Gestational diabetes in the United States: temporal changes in prevalence rates between 1979 and 2010. (11th August 2016) - Lavery, JA; Friedman, AM; Keyes, KM; Wright, JD; Ananth, CV
Abstract : Objective: To examine age–period–cohort effects on trends in gestational diabetes mellitus (GDM) prevalence in the US, and to evaluate how these trends have affected the rates of stillbirth and large for gestational age (LGA)/macrosomia. Design: Retrospective cohort study. Setting: USA, 1979–2010. Population: Over 125 million pregnancies (3 337 284 GDM cases) associated with hospitalisations. Methods: Trends in GDM prevalence were examined via weighted Poisson models to parse out the extent to which GDM trends can be attributed to maternal age, period of delivery, and maternal birth cohort. Multilevel models were used to assess the contribution of population effects to the rate of GDM. Log‐linear Poisson regression models were used to estimate the contributions of the increasing GDM rates to changes in the rates of LGA and stillbirth between 1979–81 and 2008–10. Main outcome measures: Rates and rate ratios (RRs). Results: Compared with 1979–1980 (0.3%), the rate of GDM has increased to 5.8% in 2008–10, indicating a strong period effect. Substantial age and modest cohort effects were evident. The period effect is partly explained by period trends in body mass index (BMI), race, and maternal smoking. The increasing prevalence of GDM is associated with a 184% (95% CI 180–188%) decline in the rate of LGA/macrosomia and a 0.75% (95% CI 0.74–0.76) increase in the rate of stillbirths for 2008–10, compared with 1979–81. Conclusions: The temporal increase in GDM can be attributed to period of pregnancy and age. Increasing BMI appears to partially contribute to the GDM increase in the US. Tweetable abstract: The increasing prevalence of GDM can be attributed to period of delivery and increasing maternal age. Tweetable abstract: The increasing prevalence of GDM can be attributed to period of delivery and increasing maternal age. This article includes Author Insights, a video abstract available athttps://vimeo.com/rcog/authorinsights14236 .